The Role of Integrated Positron Emission Tomography/Computed Tomography (PET/CT) and Bone Marrow Examination in Staging Large B-Cell Lymphoma. (October 2020) - Al-Sabbagh, Ahmad; Ibrahim, Feryal; Szabados, Lajos; Soliman, Dina S; Taha, Ruba Y; Fernyhough, Liam J
Introduction: In the era of routine use of positron emission tomography/computed tomography (PET/CT) for staging, it is not yet clear whether PET/CT can replace bone marrow biopsy for the assessment of bone marrow involvement in large B-cell lymphoma. Objectives: To compare the clinical utility of bone marrow biopsy and PET/CT scanning in the staging of large B-cell lymphoma. Methods: This was a retrospective analysis of all patients who presented to single center over a 4-year period with large B-cell lymphoma who had concurrent PET/CT and bone marrow biopsy performed in the assessment and staging of the lymphoma. Results: Out of 89 patients, 24 had bone marrow involvement either by PET/CT, by bone marrow biopsy, or by both. Bone marrow biopsy identified 12 patients (sensitivity 50%, specificity 100%, negative predictive value 84%), whereas PET/CT identified 23 patients (sensitivity 96%, specificity 100%, negative predictive value 98%). No patients were upstaged by the bone marrow biopsy result, and no patients had their treatment plan changed based on the bone marrow biopsy result. Conclusion: The results show that PET-CT is more sensitive and has better negative predictive value than bone marrow biopsy. This suggests that PET-CT could replace bone marrow biopsy in detecting bone marrow involvement for staging of large B-cell lymphoma.